2010
DOI: 10.1089/apc.2009.0307
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Community-Based Support Services on Clinical Efficacy and Health-Related Quality of Life in HIV/AIDS Patients in Resource-Limited Settings in Sub-Saharan Africa

Abstract: Antiretroviral therapy (ART) for HIV/AIDS in developing countries has been rapidly scaled up through directed public and private resources. Data on the efficacy of ART in developing countries are limited, as are operational research studies to determine the effect of selected nonmedical supportive care services on health outcomes in patients receiving ART. We report here on an investigation of the delivery of medical care combined with community-based supportive services for patients with HIV/AIDS in four reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 33 publications
3
64
0
Order By: Relevance
“…Though research on the role of conditional economic incentives in promoting ART adherence has been limited [68], additional studies are ongoing [69]. Food rations and livelihood support may be combined with other support services shown to improve adherence, such as treatment supporters, directly observed therapy, mobilephone text messages, and diary cards [70], and such comprehensive treatment-support programs have been shown to increase ART adherence and retention [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though research on the role of conditional economic incentives in promoting ART adherence has been limited [68], additional studies are ongoing [69]. Food rations and livelihood support may be combined with other support services shown to improve adherence, such as treatment supporters, directly observed therapy, mobilephone text messages, and diary cards [70], and such comprehensive treatment-support programs have been shown to increase ART adherence and retention [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies, reviews or editorials, research published in abstract form only or that did not undergo peer review, studies examining adherence to preor post-exposure prophylaxis or prophylaxis for the prevention of mother-to-child transmission, and any studies that did not report a measure of association between food insecurity or food assistance and adherence were excluded. Methods for the review and inclusion criteria were specified in advance, with the following additional inclusion criteria specified after the full text review: (1) definition of treatment interruption as non-adherence for at least 3 months and exclusion of papers examining treatment interruption as the outcome, (2) exclusion of two papers identified in the search that compared adherence in two groups of wasted HIV patients receiving different types of food supplements [28,29]; and (3) exclusion of studies identified in the search that evaluated combination support programs for PLHIV that included a nutritional component but did not present or permit estimation of the individual effect of food assistance distinct from the other services in the program [30][31][32][33]. Although we did not limit inclusion to adult populations, no studies examined the association between food insecurity and ART adherence in pediatric populations, and only one study examined the association between food assistance and adherence in a pediatric population [34], but was excluded because it did not specify the type of food assistance or the criteria for receiving such support.…”
Section: Study Inclusion Criteriamentioning
confidence: 99%
“…[32,33,[48][49][50] reported improvement in mobility upon initiating ART, with participants followed for the first 12 or 18 months. The study by Karbore et al [51] showed that among participants not receiving community services (i.e., food and homebased care), the mean physical functioning score increased by 1.6 points to 11.2 at 12 months but then decreased to 10.6 at 18 months, while the group which received community services improved continuously.…”
Section: Mobility (D4)mentioning
confidence: 99%
“…A number of studies have documented improved retention in care as well as better clinical outcomes using community-based or Community Home-Base Care (CHBC) models in Malawi, Haiti and elsewhere [10][11][12][13][14]. In general, CHBC includes any form of care (physical, psychosocial, palliative and spiritual) given to the sick and the affected in their own homes and care extended from the hospital or health facility to their homes through family participation and community involvement [15,16].…”
Section: Introductionmentioning
confidence: 99%